"There are risks to be taken and some just push it too far": how farmers perceive quad‐bike incident risk. (11th October 2015) - Clay, Lynne; Hay‐Smith, Jean; Treharne, Gareth; Milosavljevic, Stephan
Abstract: Objective : To qualitatively explore how farmers perceive personal risk of an occupational quad‐bike incident and develop a model of the factors that modify this perception. Methods : Grounded theory methods were used to inform data collection and analysis. Semi‐structured interviews were undertaken with eight New Zealand livestock farmers. Interviews were inductively analysed to derive categories that helped explain the processes involved in quad‐bike incident risk perception. Results : Farmers perceived personal risk of experiencing a quad‐bike incident could be modelled on a sliding scale from low to high. Four core categories encapsulated risk perception: the impact of previous quad‐bike incidents; personal attributes; getting the job done; and being familiar with the performance of the quad bike, the terrain and task(s) being undertaken. An exploratory model was developed to elucidate the temporal gap between farmers' reflections on their perceived risk and reported real‐time risk management. Conclusions : These findings have implications for planning quad‐bike safety interventions, which may benefit from incorporating both 'reflective' contemplation of risks and skills for coping with things suddenly going wrong 'in the moment'.